Brain Development and the Attention Spectrum - Itai Berger (Frontiers Research Topics, 2015)
Early-onset and enduring developmental deficits in attention, especially if combined with increased hyperactivity, and impulsivity, may result in constant impairments in multiple domains of personal life. The full spectrum of symptoms is characterized by a persistent pattern of inattention and/or hyperactivity-impulsivity, which is maladaptive and inconsistent with a comparable level of developmental age known as Attention Deficit Hyperactivity Disorder (ADHD). ADHD is considered one of the most common neurobehavioral disorders and of childhood, and among the most prevalent chronic health conditions.Given the wide heterogeneity and complex manifestations of the disorder, there is an importance in a developmental perspective that views ADHD as a multi-factorial disorder with multiple, causal processes, and pathways. The symptoms of ADHD should be cast, not as static or fixed neurobehavioral deficits, but rather in terms of underlying developmental processes.Even experienced professional might minimize the prevalence of a disorder among certain groups of patients. Therefore, the existence of attention disorders might become ""transparent"" for both the patient and the professional. This might lead to a non-accurate diagnosis, harm the treatment aspects and has potential non beneficial prognostic aspects.The developmental approach can provide predictions as to how characteristics associated with attention develop over time and how multiple risk and protective factors transact to impact it's development, as well as the development of a broad range of associated co-morbid features.Among children with mental retardation, autistic spectrum disorders, children who were born premature, born with low birth weight, as well as among those who suffer from chronic disorders (such as epilepsy, diabetes, chronic kidney disease or asthma), as well as among otherwise healthy preschoolers - the assessment of attention performance might be very challenging. In this research topic, we explore the latest cutting edge research on the biological and neural pathways as well as on psychosocial and behavioral correlates of brain development and attention spectrum. In doing so we aim to highlight: what is currently known regarding this new conceptualization of attention as a spectrum; the mechanisms underlying this spectrum; and where this field is headed in terms of developing our understanding of the link between brain development and attention performance.